Karakteristik gejala klinis kehamilan dengan Coronavirus disease (COVID-19) - Luluk Windra Yuliana (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Coronavirus disease 2019 (COVID-19) is an acute respiratory infection that spreads rapidly in globally by a short time. COVID-19 is caused by a novel coronavirus known as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). This virus is a single-chain RNA. Transmission of virus spreads very rapidly through human-to-human contact via respiratory droplets and saliva from people infected with COVID-19. The clinical symptoms of COVID-19 can be symptomatic and asymptomatic. The World Health Organization (WHO) divides the symptomatic clinical symptoms of COVID-19 into mild, moderate, severe, and critical conditions. This paper aims to determine the clinical picture of pregnant women with COVID-19 infection. This research method is to review articles published in the last 1 year with the keywords pregnancy, COVID-19, clinical symptoms, and coronavirus. Data shows that the majority of pregnant women with COVID-19 have mild clinical symptoms, where the main symptoms that appear are fever, cough, and dyspnea. Gestational age does not determine the severity of the clinical symptoms of pregnant women and on average pregnant women with COVID-19 have a short duration of hospitalization